Nucleosome plasticity is a critical element of chromatin liquid–liquid phase separation and multivalent nucleosome interactions - Stephen E. Farr (Nature Portfolio, 2021)
Resolving nucleosomes with chemical accuracy inside sub-Mb chromatin provides molecular insight into the modulation of chromatin structure and its liquid–liquid phase separation (LLPS). By developing a multiscale chromatin model, the authors find that DNA breathing enhances the valency, heterogeneity, and dynamics of nucleosomes, promoting disordered folding and LLPS.